Fishery Service Empowerment In Business Opportunity For Fish Crackers of Increasing Family Revenues in the Gisikcemandi at Sedati Sub District,Sidoarjo District, Indonesia - Yuniningsih Yuniningsih; Dwi Suhartini (Future Science)
Utilization of the potential or local wisdom of a village by the community if managed properly will be a source of income. The purpose of community service is the empowerment of the community in utilizing the processed marine fish in making fish crackers. Implementation of dedication in Gisik Cemandi hamlet is because fishing communities mostly tend to rely on fish catches for sale directly. Based on these conditions it is done dedication in improving the processed fish. This incident is done by counseling and training in making fish crackers, especially made from milkfish. Participants of extension and training as many as 30 divided into 6 groups consisting of locals, especially mothers. The outcomes and training are expected to provide housewives skills. Skills acquired can be developed to open a business of making crackers that impact on increasing opinions and family welfare.